If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9x-(8x+7)=9x-(-7+6x)
We move all terms to the left:
-9x-(8x+7)-(9x-(-7+6x))=0
We add all the numbers together, and all the variables
-9x-(8x+7)-(9x-(6x-7))=0
We get rid of parentheses
-9x-8x-(9x-(6x-7))-7=0
We calculate terms in parentheses: -(9x-(6x-7)), so:We add all the numbers together, and all the variables
9x-(6x-7)
We get rid of parentheses
9x-6x+7
We add all the numbers together, and all the variables
3x+7
Back to the equation:
-(3x+7)
-17x-(3x+7)-7=0
We get rid of parentheses
-17x-3x-7-7=0
We add all the numbers together, and all the variables
-20x-14=0
We move all terms containing x to the left, all other terms to the right
-20x=14
x=14/-20
x=-7/10
| 6=0.06*100+b | | 4x+5)=(x^2-27 | | 1778=3x-150 | | X+3x+x-2=78 | | (2x+10)(2x-50)(x-40)=180 | | 50+-1x=x+66 | | 6(2x+4=(3x+6 | | 1)y+6=20 | | T=4s+4.03 | | T=4s+4.03s | | 220.00+0.15m=299.50 | | 8(x-5)+29=7x-6 | | 8(x-2)+3=8x-12 | | 6(x-8)+40=6x-8 | | -10−4g=-6g | | 18x−3x^2=0 | | -7v+3=-7−6v | | -5k=-7k−10 | | X(x-1)=200 | | 2−7u=-5u+6 | | 7r+21=44r | | 5r+10=-5+2r | | 29=257-x | | 4k+10=5k | | 10r=8+8r | | 14+25f=35+16f | | -12p39=11(p+14) | | -2−6v=-5v | | (d/5)+3D-10=(1/3)d+33 | | D/5+3D-10=(1/3)d+33 | | 1/6y-4=-11 | | -3b=-2b−9 |